2017
DOI: 10.1177/8756870517721693
|View full text |Cite
|
Sign up to set email alerts
|

Reaching Out to Paraprofessionals: Engaging Professional Development Aligned With Universal Design for Learning Framework in Rural Communities

Abstract: The literature reveals that paraprofessionals are responsible for supporting students at risk of/with disabilities in a variety of academic and nonacademic tasks, yet they often lack appropriate training. Recent studies demonstrated the effectiveness of training for paraprofessionals to support students with disabilities in a meaningful way. In rural communities, such professional development and training opportunities are often unavailable despite the need. The purpose of this study was to explore the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Interview data from a qualitative study showed that some paraeducators did not receive any training in autism prior to working with a student with autism, and other paraeducators disclosed using a trial-and-error approach when working with students with autism, due to a lack of training (Giles, 2009). Paraeducators who did receive training learned information about assistive technology and evidence-based practices; principles to support behavior management, communication, and small group instruction; strategies for meaningful inclusion; and strategies for behavior management (Barrio & Hollingshead, 2017). In contrast to in-service professional development training, one study found that most paraeducators were trained for their positions as paraeducators on the job, in which they learned about educational terminology, programs, roles, instructional activities, purposes of programs, effects of disabilities on student functioning, and ethics (Carter et al, 2009).…”
Section: Training and Autism-focused Professional Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Interview data from a qualitative study showed that some paraeducators did not receive any training in autism prior to working with a student with autism, and other paraeducators disclosed using a trial-and-error approach when working with students with autism, due to a lack of training (Giles, 2009). Paraeducators who did receive training learned information about assistive technology and evidence-based practices; principles to support behavior management, communication, and small group instruction; strategies for meaningful inclusion; and strategies for behavior management (Barrio & Hollingshead, 2017). In contrast to in-service professional development training, one study found that most paraeducators were trained for their positions as paraeducators on the job, in which they learned about educational terminology, programs, roles, instructional activities, purposes of programs, effects of disabilities on student functioning, and ethics (Carter et al, 2009).…”
Section: Training and Autism-focused Professional Developmentmentioning
confidence: 99%
“…In contrast to in-service professional development training, one study found that most paraeducators were trained for their positions as paraeducators on the job, in which they learned about educational terminology, programs, roles, instructional activities, purposes of programs, effects of disabilities on student functioning, and ethics (Carter et al, 2009). Furthermore, paraeducators have indicated a need for additional information on individual qualities or attributes associated with the 13 IDEA disability categories, particularly autism, specifically requesting for more information about emotional and behavioral problems for students with autism (Barrio & Hollingshead, 2017).…”
Section: Training and Autism-focused Professional Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although paraprofessionals are valuable in supporting student success for students with disabilities in general education settings, overreliance on school staff may hinder opportunities for relationship development (Giangreco & Broer, 2005). In addition, overreliance of paraprofessionals may (a) lead to general education teachers to rely on paraprofessionals to deliver instruction of curricular content, (b) physically isolate students with disabilities form their peers, (c) limit development of independent skills, and (d) impede naturally occurring peer-to-peer interaction (Barrio & Hollingshead, 2017; Carter et al, 2015; Giangreco & Broer, 2005). When peer support arrangements are utilized, the role of the paraeducator moves from delivering instruction directly to the student to more of a facilitator and support role (Carter et al, 2015).…”
Section: Predictors Of Postschool Successmentioning
confidence: 99%
“…Also, teachers—personnel ultimately responsible for the implementation of many EBPs—may not be receiving sufficient preservice training on implementation of EBPs (Morrier et al, 2011), and stand-alone professional development trainings have proven limited in effectiveness without follow-up implementation supports such as coaching (Kretlow & Bartholomew, 2010). Yet, online learning resources offer a cost-effective means of support for practitioners and school professionals to learn about practices on their own or as teams (Barrio & Hollingshead, 2017; Da Fonte & Capizzi, 2015).…”
Section: Support For Implementation Of Ebpsmentioning
confidence: 99%